2020
DOI: 10.1049/iet-rpg.2020.0580
|View full text |Cite
|
Sign up to set email alerts
|

Value of bifacial photovoltaics used with highly reflective ground materials on single‐axis trackers and fixed‐tilt systems: a Danish case study

Abstract: The energy produced by bifacial photovoltaic (PV) arrays can be augmented via albedo enhancements. However, the value of the additional energy must outweigh the costs for such modifications to be economically viable. In this work, the electrical performance and economic value of six 13 kWp crystalline‐silicon (c‐Si) PV arrays with distinct configurations are evaluated. The system designs include horizontal single axis trackers (HSAT) and 25° fixed‐tilt structures, monofacial and bifacial PV panels, and low and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The testbed shown in Fig. 1(a) is located near Roskilde, Denmark (55.6°N, 12.1°E) within the Technical University of Denmark's (DTU) outdoor PV test facility [18] [22]. The 25° fixed-tilt 14.2 kWp grid-tied array contains 24 large-area bifacial PERC (passivated emitter and rear cell) modules that became commercially available in 2021.…”
Section: A Outdoor Measurement Platformmentioning
confidence: 99%
“…The testbed shown in Fig. 1(a) is located near Roskilde, Denmark (55.6°N, 12.1°E) within the Technical University of Denmark's (DTU) outdoor PV test facility [18] [22]. The 25° fixed-tilt 14.2 kWp grid-tied array contains 24 large-area bifacial PERC (passivated emitter and rear cell) modules that became commercially available in 2021.…”
Section: A Outdoor Measurement Platformmentioning
confidence: 99%
“…Patel et al [37] found that for systems with modulerelated costs higher than land-related costs and project latitude higher than 30 • , the tilt angle of bifacial photovoltaic modules is 10 • -45 • , and the LCOE can be reduced by 2-6%. Riedel-Lyngskaer et al [38] pointed out that, compared to the optimal fixed-tilt mounted system, a horizontal single-axis tracker system can reduce the LCOE by 3.5 EUR/MWh, and a bifacial photovoltaic module can reduce LCOE by 4.0 EUR/MWh. Furthermore, the high cost and structural complexity have limited the wide application of dual-axis tracker.…”
Section: Introductionmentioning
confidence: 99%
“…Bifacial modules can convert irradiance from the front and rear side, enabling higher energy yields without more complicated fabrication procedures. [20][21][22][23][24][25][26][27][28][29][30][31] Consequently, the market share of bifacial modules has dramatically increased from 2% in 2016 32 to 28% in 2021 33 and is projected to grow to about 60% by 2032, 33 indicating the need to update the standard to bifacial modules.…”
mentioning
confidence: 99%